Pronouncing Shakespeare the Globe experiment - Crystal, David 1941- (Cambridge University Press, 2005)
How did Shakespeare's plays sound when they were originally performed? How can we know, and could the original pronunciation ever be recreated? For three days in June 2004 Shakespeare's Globe presented their production of Romeo and Juliet in original, Shakespearian pronunciation. In an unusual blend of autobiography, narrative, and academic content, reflecting the unique nature of the experience, this 2005 book by David Crystal recounts the first attempt in over 50 years to mount a full-length Shakespeare play in original pronunciation. Crystal begins by discussing the Globe theatre's approach to 'original practices', which has dealt with all aspects of Elizabethan stagecraft - except pronunciation. A large section is devoted to the nature of the Early Modern English sound system. There are reports of how the actors coped with the task of learning the pronunciation, how it affected their performances and how the audiences reacted